2021
DOI: 10.1101/2021.04.27.21256099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sentinel seroprevalence of SARS-CoV-2 in the Gauteng province, South Africa August to October 2020

Abstract: Background: Estimates of prevalence of anti-SARS-CoV-2 antibody positivity (seroprevalence) are for tracking the Covid-19 epidemic and are lacking for most African countries. Objectives: To determine the prevalence of antibodies against SARS-CoV2 in a sentinel cohort of patient samples received for routine testing at tertiary laboratories in Johannesburg, South Africa Methods: This sentinel study was conducted using remnant serum samples received at three National Health Laboratory Services laboratories situat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The similarities between public-and private-sector R estimates are of particular interest in light of several seroprevalence studies which suggest that clients of the public sector experienced higher levels of SARS-CoV-2 transmission [7,31,38]. It is also important to note the under-representation of clients of the public sector in all three data endpoints relative to clients…”
Section: Public Versus Private Sectormentioning
confidence: 89%
See 1 more Smart Citation
“…The similarities between public-and private-sector R estimates are of particular interest in light of several seroprevalence studies which suggest that clients of the public sector experienced higher levels of SARS-CoV-2 transmission [7,31,38]. It is also important to note the under-representation of clients of the public sector in all three data endpoints relative to clients…”
Section: Public Versus Private Sectormentioning
confidence: 89%
“…However, aside from the regular reports we released via the National Institute for Communicable Diseases (NICD) [23], the studies we identified relied on publicly reported time series data, which do not include symptom onset dates and which may be affected by backfilling and additional reporting delays, and used international estimates for the generation interval [1,2,[24][25][26][27][28][29][30]; most studies also use a single measure of incidence and do not cover all of the first four waves. While currently available evidence suggests that clients of the public sector experienced higher levels of transmission during the first two waves [7,31], we did not identify any studies comparing reproduction number estimates in different income groups, or between healthcare sectors.…”
Section: Plos Onementioning
confidence: 95%
“…The similarities between public- and private-sector R estimates are of particular interest in light of several seroprevalence studies which suggest that clients of the public sector experienced higher levels of SARS-COV-2 transmission [ 7 , 22 , 39 ], as well as the under-representation of clients of the public sector in all three data endpoints relative to clients of the private sector – clients of the private sector make up approximately 17% of the South African population, while only 52% of recorded cases were in the private sector.…”
Section: Discussionmentioning
confidence: 99%
“…However, aside from the regular reports we released via the National Institute for Communicable Diseases (NICD) [ 14 ], the studies we identified relied on publicly reported time series data, which do not include symptom onset dates and which may be affected by backfilling and additional reporting delays, and used international estimates for the generation interval [ 1 , 2 , 15 – 21 ]; most studies also use a single measure of incidence and do not cover all of the first four waves. While currently-available evidence suggests that clients of the public sector experienced higher levels of transmission during the first two waves [ 7 , 22 ], we did not identify any studies comparing reproduction number estimates in different income groups, or between healthcare sectors. R estimates are typically based on time series data of cases or deaths, though any measure representing an approximately constant proportion of total incidence may be used, in conjunction with data from which to estimate the generation interval [ 23 ].…”
Section: Introductionmentioning
confidence: 99%